Negotiating Traditional Masculinity in A Man Called Otto (2022) - Zahra, Rahma Ani Qotuz (Universitas Negeri Surabaya, 2025)
Traditional Masculinity remains a dominant ideal, emphasizing traits such as independence, emotional restraint, and isolation. This study aims to analyze how the character Otto in the film A Man Called Otto (2022) represents and negotiates traditional masculinity. Using R.W. Connell’s theory of hegemonic masculinity (2005), the analysis explores Otto’s transformation through his interactions with Marisol. This gradually led him to adopt values of emotional openness, interdependence, and connection. Otto’s journey illustrates a shift from rigid masculine norms to a more relational identity.